Linguistic Effort Of Abdulrahman Alhaj Saleh And Tamam Hassan And Its Influence On Arabic Teaching/ الجهود اللسانية عند عبد الرحمن الحاج صالح وتمام حسان وأثره في تعليم اللغة العربية - Bilal Azzouz; Fetati Fatna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Linguistics since its infancy has interested in studying the language in a scientific way, by attempting to comprehensively capture all language issues whether by regulating its physical vocal or the interpretation of its words. In addition to its semantic and grammatical composition. Arabs had a significant share in these studies and research in recent and old time, and their literature are rich of that. For example the modern Arab intellectualswho have had a clear imprint on this science, there are two researchers who talked about various linguistic issues, the first from Maghreb the scholar and the scientist Abdulrahman Haj Saleh and the second from the eastern Arab world, the linguistic scientist Tamam Hassan . This research aims to look into the linguistic study which those two scholars by theory to the modern theory, also this research focuses on the basic concepts of the modern Khalili theory and the cognitive systematic theoretical orientation in studying Arabic grammar in all its aspects and informations, also we followed the descriptive method with the analysis mechanism to explore the most important in what those scholars gave into the Arabic language lesson.